Implementation of the Literacy and Numeracy Habituation Program to Improve Students' Basic Competencies - Mirajul Wathoni; Muh Deni Siregar; Novina Anjalina Nur Anisa; Fathimatuzzuhro Lathif; Herlina Yanti; Hikatun Fatmariza (Generasi Sains Indonesia, 2026)
This study aims to analyze the implementation of a Literacy and Numeracy Habituation Program (Bias Litnum) and its impact on students’ foundational competencies in an elementary school context. A qualitative descriptive approach was employed, involving classroom observations, semi-structured interviews, and document analysis to capture instructional processes and student learning experiences. The findings reveal that the program, implemented through routine, contextual, and student-centered activities, contributes to improvements in reading comprehension, writing skills, and numeracy reasoning. The results also indicate that adaptive teacher facilitation and supportive learning environments play a critical role in enhancing student engagement and participation. The novelty of this study lies in its integrated analysis of literacy and numeracy within a habituation-based framework, highlighting the interaction between routine practice, contextual learning, and student engagement as key mechanisms for developing foundational competencies. The study provides both theoretical and practical implications by proposing a holistic approach to literacy and numeracy development that goes beyond traditional instructional models. These findings suggest that habituation-based programs can serve as an effective and sustainable strategy for improving basic competencies in elementary education.